2012
DOI: 10.1111/j.1553-2712.2012.01361.x
|View full text |Cite
|
Sign up to set email alerts
|

A Medical Simulation‐based Educational Intervention for Emergency Medicine Residents in Neonatal Resuscitation

Abstract: Objectives: The objective was to determine if a medical simulation-based neonatal resuscitation educational intervention is a more effective teaching method than the current emergency medicine (EM) curriculum at one 4-year EM residency program.Methods: A prospective, randomized study of second-, third-, and fourth-year EM residents was performed. Of 36 potential subjects, 27 residents were enrolled. Each resident was assessed at baseline and after the intervention using 1) a questionnaire to evaluate confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 24 publications
0
61
0
Order By: Relevance
“…Research methodology included 17 surveys (36%), 17,19,21,25,30,31,33,37,40,42,46,[50][51][52]54,60,61 15 (31%) observational analyses, [14][15][16]22,23,27,32,33,38,44,47,49,56,57,59 and three (6%) qualitative methodology studies. 19,28,45 There were only 12 (25%) with an experimental or quasi-experimental study design, 20,24,26,35,36,39,41,43,48,53,55,57 with five of the highlighted articles using this rigorous design. 35,36,41,…”
Section: Trends In Medical Education Research In 2012mentioning
confidence: 99%
See 3 more Smart Citations
“…Research methodology included 17 surveys (36%), 17,19,21,25,30,31,33,37,40,42,46,[50][51][52]54,60,61 15 (31%) observational analyses, [14][15][16]22,23,27,32,33,38,44,47,49,56,57,59 and three (6%) qualitative methodology studies. 19,28,45 There were only 12 (25%) with an experimental or quasi-experimental study design, 20,24,26,35,36,39,41,43,48,53,55,57 with five of the highlighted articles using this rigorous design. 35,36,41,…”
Section: Trends In Medical Education Research In 2012mentioning
confidence: 99%
“…19,28,45 There were only 12 (25%) with an experimental or quasi-experimental study design, 20,24,26,35,36,39,41,43,48,53,55,57 with five of the highlighted articles using this rigorous design. 35,36,41,43,55 These trends are summarized in Table 3.…”
Section: Trends In Medical Education Research In 2012mentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Lee and colleagues evaluated the change in score achieved on a validated neonatal resuscitation scoring tool among emergency medicine residents who undertook neonatal resuscitation simulation training compared to residents exposed to a traditional curriculum. 19 They concluded that simulation-based educational interventions may be used to improve emergency medicine residents' knowledge of and performance with neonatal resuscitation. Allan and colleagues described and evaluated an interprofessional simulation-based educational program within a busy 24-bed pediatric cardiac intensive care unit.…”
mentioning
confidence: 99%